Biosensor development as an alternative test for Leptospirosis diagnosis: a systematic review - Susanti Susanti; Radiana Dhewayani Antarianto (Indonesian Archives and Biomedical Sciences, 2021)
Leptospirosis is a zoonotic disease caused by pathogenic bacteria from the genus Leptospira that can attack livestock, wild animals, and humans. The diagnosis of leptospirosis is currently carried out by Leptospira culture, Microscopic Agglutination Test (MAT), Enzyme Linkage Immunosorbent Assay (ELISA), and Polymerase Chain Reaction (PCR). This test requires a specific laboratory, long test time, experienced personnel, a lot of equipment and is expensive and difficult to apply in the field. Biosensor technology is a necessary method of disease diagnosis to detect biomolecules such as protein and bacteria biomarkers. The purpose of this article is to provide information on the development of biosensors as an alternative test for the diagnosis of leptospirosis. The method used is a systematic review using the PRISMA protocol. The results showed that the electrochemical biosensor with monoclonal anti-LipL32 and ssDNA probe specific to the LipL32 gene of Leptospira had advantages for leptospirosis diagnosis because it was cheap, accurate, portable, small test equipment, and capable of detecting leptospirosis. Optical biosensors (specifically lateral flow systems, magnetogenosensors and paper fluidic devices) can detect Leptospira bacteria with sensitive, specific, easy manipulation, and users can get fast visual test results within minutes. This biosensor technology can be used as a promising alternative diagnostic method for the diagnosis of leptospirosis with simplicity, high sensitivity, fast detection time, low cost, and portable so that it is easy to apply in the field.